Influence Of High-Performance Work System On Employee Performance And Mediating Role Of Employee Engagement - Rahman A, Alshammari Tai Abdul (2024)
The aviation industry consistently enhances its human resources by recruiting and retaining proficient personnel. The implementation of a structured Human Resource Management (HRM) program is deemed essential in the aviation industry, as it is regarded as a pivotal element of organizational activities. The top management of the aviation industry has been engaging in recruitment efforts, however, a significant proportion of the newly hired personnel have tended to discontinue their employment within a brief timeframe. Modern service managers acknowledge that allocating resources toward employee investment and fostering a supportive work environment can result in heightened motivation, superior job performance, and decreased employee turnover. High-performance work practices (HPWPs) are defined as human resource activities that have a positive impact on employee performance. Therefore, the main objective of this dissertation is to investigate the impact of HPWS on employee performance, a consensus on the mechanisms underlying this relationship has yet to be reached. The present study employs Social Exchange Theory (SET) to examine the relationship between High-Performance Work Systems (HPWS) and employee performance, with a focus on exploring the mediating effect of employee engagement.